Faktor-Faktor Yang Mempengaruhi Penduduk Miskin Di Kecamatan Kota Kefamenanu Kabupaten Timor Tengah Utara - Emilia Khristina Kiha; Berno Benigno Mitang (Ekopem: Jurnal Ekonomi Pembangunan, 2019)
ABSTRACT This study aims to analyze factors effecthing poverty in the District of North Central Timor. The factors are including outpouring of working hours, education, age and family size. The research was conducted in the District of Kefamenanu city to the number of households in the district of Kefamenanu as many as 2149 families, with a sample of 96 families. The instrument of data collection used questionnaires and interviews. Analysis of the data used is Ordinary Least Square (OLS) using instrument of SPSS 16.0. The results showed that the variables of outpouring of working hours, education, age and family size have a significant positive impact on poverty. Keywords: Poverty, Outpouring Of Working Hours, Education, Age and Family Size.